A comparison of Matura rates and academic performance using the example of the University of St.Gallen - Zwingenberger, Anja; Obrecht, Samuel (Swiss Journal of Educational Research, 2018)
Debates over the «appropriate» number of Swiss academics Matura graduates stand at the center of current discussions of education policy.The present empirical study investigates a possible link between Matura rates that vary by canton and the academic performance of students, using the example of the entrance year at the University of St.Gallen. Using regression and rank sum tests, data from a total of n=5,914 students with Swiss Matura certificates in the period 2003 to 2012 was analyzed. The statistical analyzes performed show that students from cantons with higher Matura rates exhibit poorer academic performance on average. The academic performance of those who «successfully» complete the first year does not statistically differ in terms of Matura rates. A significant negative effect of high school Matura rate on academic performance can be established with regard to the sub-group of students who did not pass the entrance year.Based on the statistical robustness of the effects, one can speak of an explicit signal via a connection between the level of the Matura rate and academic performance. However, the extent of this effect is weak, something that must be considered in the discussion of regional, social and political factors.